Role of Myeloperoxidase, Oxidative Stress, and Inflammation in Bronchopulmonary Dysplasia - Tzong-Jin Wu; Xigang Jing; Michelle Teng; Kirkwood A. Pritchard; Billy W. Day; Stephen Naylor; Ru-Jeng Teng (MDPI AG, 2024)
Bronchopulmonary dysplasia (BPD) is a lung complication of premature births. The leading causes of BPD are oxidative stress (OS) from oxygen treatment, infection or inflammation, and mechanical ventilation. OS activates alveolar myeloid cells with subsequent myeloperoxidase (MPO)-mediated OS. Premature human neonates lack sufficient antioxidative capacity and are susceptible to OS. Unopposed OS elicits inflammation, endoplasmic reticulum (ER) stress, and cellular senescence, culminating in a BPD phenotype. Poor nutrition, patent ductus arteriosus, and infection further aggravate OS. BPD survivors frequently suffer from reactive airway disease, neurodevelopmental deficits, and inadequate exercise performance and are prone to developing early-onset chronic obstructive pulmonary disease. Rats and mice are commonly used to study BPD, as they are born at the saccular stage, comparable to human neonates at 22-36 weeks of gestation. The alveolar stage in rats and mice starts at the postnatal age of 5 days. Because of their well-established antioxidative capacities, a higher oxygen concentration (hyperoxia, HOX) is required to elicit OS lung damage in rats and mice. Neutrophil infiltration and ER stress occur shortly after HOX, while cellular senescence is seen later. Studies have shown that MPO plays a critical role in the process. A novel tripeptide, N-acetyl-lysyltyrosylcysteine amide (KYC), a reversible MPO inhibitor, attenuates BPD effectively. In contrast, the irreversible MPO inhibitor-AZD4831-failed to provide similar efficacy. Interestingly, KYC cannot offer its effectiveness without the existence of MPO. We review the mechanisms by which this anti-MPO agent attenuates BPD.